Is Autologous Stem Cell Transplantation a Safe and Effective Alternative to Whole Brain Radiation as Consolidation Therapy in Patients With Primary Central Nervous System Lymphoma?: A Critically Appraised Topic. Issue 4 (July 2021) - Gritsch, David; Mrugala, Maciej M.; Marks, Lisa A.; Mangipudi, Kartik; Neal, Matthew; Wingerchuk, Dean M.; O'Carroll, Cumara B.
Abstract : Background: High-dose chemotherapy followed by autologous stem cell transplantation (HD-ASCT) is a promising alternative to whole brain radiation therapy (WBRT) in the treatment of primary central nervous system lymphoma (PCNSL). The objective of this study was to critically assess current evidence supporting the use of HD-ASCT as first-line consolidative therapy in PCNSL. Methods: The objective was addressed through the development of a critically appraised topic that included a clinical scenario, structured question, literature search strategy, critical appraisal, assessment of results, evidence summary, commentary, and bottom-line conclusions. Participants included consultant and resident neurologists, a medical librarian, clinical epidemiologists, and a content expert in the field of neuro-oncology. Results: A recent, open-label, noncomparative randomized phase II trial was selected for critical appraisal. This trial evaluated the efficacy and toxicity of consolidative therapy with HD-ASCT and WBRT in PCNSL in 2 separate treatment arms. A total of 140 patients with newly diagnosed PCNSL between the ages of 18 and 60 years were included. The primary endpoint of 2-year progression-free survival was met in 63% of patients in the WBRT arm and 87% in the HD-ASCT arm. Notably, an overall improvement in neurocognitive scores was observed following HD-ASCT, while WBRT was associated with worsened cognitive outcomes. Conclusions: In young patients with newly diagnosed PCNSL, consolidative therapy with HD-ASCT appears to be associated with less neurocognitive toxicity and may be more effective than WBRT at preventing relapses, however, at the cost of a higher treatment-related mortality.